A STUDY ON FACTORS CONTRIBUTING TO FARMERS’ ADOPTION OF AGRICULTURAL MACHINERY IN SALEM DISTRICT - C. Manikkal; B. Sudha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian agriculture has marked its presence in the world. It ranks among the best countries in the world for the production of a number of crops, including rice, wheat, sugar cane, fruits and vegetables. Agriculture contributes 26 percent of national income. Therefore, India’s prosperity depends on agricultural prosperity. Although the opportunities in the agricultural equipment sector in India are immense, the sector faces challenges on several fronts. Unlike other agricultural sectors, the agricultural mechanization sector has a much more complex structural composition. The mechanization of farms depends on factors such as capital and interest rates, lack of data, small size and dispersion of land, etc. The Indian government has encouraged mechanization through various policy interventions. The technologies that have evolved in the agricultural machinery sector in recent years have enormous potential to realize the vision of the “Make in India” initiative which promotes innovation and investment. The trend paved the way for a range of agricultural tools. This has resulted in a shift from the traditional agricultural process to a more mechanized one. Although the level of mechanization in India is lower than that of other developed countries, it is certainly increasing. This paper discusses farmers’ perceptions of the use of agricultural equipment in Salem district.